The Strategy for Preservation and Development of the Historical Heritage of the RF: Рroblems and Their Solutions - Kudryavtsev, Alexander (project baikal, 2016)
National cultural heritage is a key element of the social, economic and intellectual potential of Russia. The masterpieces of the historical and material culture are symbols of the nation. The existing legislative and regulatory basis ensures preservation of the cultural heritage. However, it is hard to overcome the negative dynamics of the irreparable loss of the cultural heritage sites – the wooden architecture, the works of the avant-garde, the 1930-1950s, the Soviet Modernism. The historical environment disappears in small and medium towns. The article gives several positive examples of dealing with the historical heritage, including the alternative methods of economical management of cultural heritage properties. The leading role in heritage preservation belongs to the town-planning factor in the system of preservation, the rise of the authorities’ responsibility, and cooperation between the state and the civil society.